2021
DOI: 10.3390/vaccines9111280
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Therapeutic Response to Intralesional Bivalent HPV Vaccine in Wart Immunotherapy

Abstract: Variable intralesional immunotherapies have recently been proposed as a means of achieving a successful eradication of recurrent and recalcitrant human papillomavirus (HPV)-induced cutaneous and anogenital warts. The bivalent HPV vaccine is one of the newly proposed immunotherapeutic agents. We investigated the role of interleukin-4 (IL-4) and interferon-gamma (IFN-γ) as ex vivo immunologic predictors to estimate the response to the bivalent HPV vaccine as a potential immunotherapy for cutaneous and anogenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Immunotherapy based on the Th1 immune response, such as imiquimod and interferon, showed a curative effect in HPV infection. Studies have also shown that the failure of immunotherapy is related to Th2 cytokine profiles, such as IL-4 and IL-10, which indicates that topical Th1/Th2 imbalance might lead to warts ( 9 ). However, in patients with atopic dermatitis, the use of the IL-4 inhibitor dupilumab may lead to the aggravation of diseases dominated by the Th1/Th17 axis, such as psoriasis and multiple sclerosis ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy based on the Th1 immune response, such as imiquimod and interferon, showed a curative effect in HPV infection. Studies have also shown that the failure of immunotherapy is related to Th2 cytokine profiles, such as IL-4 and IL-10, which indicates that topical Th1/Th2 imbalance might lead to warts ( 9 ). However, in patients with atopic dermatitis, the use of the IL-4 inhibitor dupilumab may lead to the aggravation of diseases dominated by the Th1/Th17 axis, such as psoriasis and multiple sclerosis ( 10 ).…”
Section: Discussionmentioning
confidence: 99%